Implementation of Notary Liability in The Making of Deed Based Act No. 2 of 2014 on Notary Position - Syafiera Amelia; Rudi Hendri Basuki; Aryani Witasari (Jurnal Akta, 2019)
This study aims to investigate the Implementation Of Notary Liability In The Making Of Deed Based Act No. 2 Of 2014 On  Notary Position and how protection Notary Notaries in deed.This study uses normative legal or sociological approach, as this study does not only include the Legislation and legal materials in the library, but also to the practice field as the supporting data. Also in this study are also used as the primary data source supporting data in a finding that will be examined with regard to liability notarized under Act No. 2 of 2014 concerning Notary.The results of this study ultimately provide answers form of accountability in the manufacture of a notarial deed notary if a notary to make mistakes as well as a form of protection notary if one were sued by applicant. Implementation responsibilities of office owned by a Notary is not done, then it could result in a deed made void, canceled by the parties or the deed only a proofing tool contract under hand. Because the deed deed null and void, the reason for the parties who suffered damages to sue replacement costs, damages and interest to the Notary. MKN Notary protection given to the Notary that if one made the call by the court to a Public Notary, must request permission in advance to MKN, should be make coordination with INI organization or Competent Senior Notary.Keywords: Notaries; Public Notary Accountability; Deeds.